Adjustment and mental health problem in prisoners - Sinha, Sudhinta (Medknow Publications & Media Pvt Ltd, 2010)
BACKGROUND: “Crime” is increasing day by day in our society not only in India but also all over the world. In turn, the number of prisoners is also increasing at the same rate. They remain imprisoned for a long duration or in some cases for the whole life. Living in a prison for long time becomes difficult for all inmates. So they often face adjustment and mental health problems. Recent findings suggest that mental illness rate in prison is three times higher than in the general population. OBJECTIVE: The aim of the present study was to investigate the adjustment and the mental health problem and its relation in the prisoners. MATERIALS AND METHODS: In the present study, 37 male prisoners of district jail of Dhanbad District of Jharkhand were selected on purposive sampling basis. Each prisoner was given specially designed Performa – Personal Data Sheet, General Health Questionnaire-12 and Bell Adjustment Inventory. Appropriate statistical tools were used to analyze the data. RESULTS: The results obtained showed poor adjustment in social and emotional areas on the adjustment scale. The study also revealed a significant association between adjustment and mental health problem in the prisoners. CONCLUSION: The prisoners were found to have poor social and emotional adjustment which has strong association with their mental health.